2009
DOI: 10.1128/jb.01210-08
|View full text |Cite
|
Sign up to set email alerts
|

Defects in the Error Prevention Oxidized Guanine System Potentiate Stationary-Phase Mutagenesis in Bacillus subtilis

Abstract: Previous studies showed that a Bacillus subtilis strain deficient in mismatch repair (MMR; encoded by the mutSL operon) promoted the production of stationary-phase-induced mutations. However, overexpression of the mutSL operon did not completely suppress this process, suggesting that additional DNA repair mechanisms are involved in the generation of stationary-phase-associated mutants in this bacterium. In agreement with this hypothesis, the results presented in this work revealed that starved B. subtilis cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 47 publications
8
58
0
Order By: Relevance
“…Cells deficient for mutT, yvcI, or yjhB showed virtually no change in mutation frequency relative to a wild-type strain; a similar result occurred when all three genes were disrupted (355,356). There is evidence suggesting that the ytkD gene may encode an activity that is similar to that of E. coli MutT (55,324,428). It was shown that YtkD can specifically hydrolyze 8-oxo-(d)GTP, as well as complement a mutT deficiency in E. coli.…”
Section: The "Go" Systemmentioning
confidence: 59%
See 1 more Smart Citation
“…Cells deficient for mutT, yvcI, or yjhB showed virtually no change in mutation frequency relative to a wild-type strain; a similar result occurred when all three genes were disrupted (355,356). There is evidence suggesting that the ytkD gene may encode an activity that is similar to that of E. coli MutT (55,324,428). It was shown that YtkD can specifically hydrolyze 8-oxo-(d)GTP, as well as complement a mutT deficiency in E. coli.…”
Section: The "Go" Systemmentioning
confidence: 59%
“…It was shown that YtkD can specifically hydrolyze 8-oxo-(d)GTP, as well as complement a mutT deficiency in E. coli. It was also shown that cells deficient for ytkD are more susceptible to oxidative DNA damage (55,324,428). However, others have presented evidence that YtkD fails to hydrolyze 8-oxo-dGTP selectively over dGTP (458).…”
Section: The "Go" Systemmentioning
confidence: 99%
“…In agreement with this idea, it has been shown that the genetic inactivation of the mismatch (MMR) and guanine-oxidized (GO) systems potentiates the mutagenic events that occur in nongrowing B. subtilis cells (6,7). Thus, it appears that the accumulation of mismatched and oxidized DNA bases in nongrowing B. subtilis cells is a key factor that promotes mutations under conditions of nutritional or metabolic stress (6,7).…”
mentioning
confidence: 52%
“…General and specific DNA repair systems, mismatch repair, and oxidative damage repair (GO system) have been shown to be repressed or inefficient in cells under conditions of stress in eukaryotic and bacterial systems (19,25,28,45) while errorprone polymerases are active in stationary-phase cells (11,12,19,42,43). Thus, one can speculate that the combination of transcriptional derepression and DNA repair inadequacies under conditions of nongrowth biases mutations to transcribed regions.…”
Section: Resultsmentioning
confidence: 99%
“…Spontaneous cellular processes such as deamination, oxidation, and base loss generate uracil, 8-oxo-7,8-dihydroguanine (8-oxoG), and apurinic/apyrimidinic (AP) sites in DNA, respectively (reviewed in reference 37). Of these DNA-insulting processes, those causing oxidative damage have been shown to be significant in B. subtilis cells under conditions of starvation (45). The ability of RNA polymerase to bypass these and perhaps other types of lesions may result in base misinsertion in the transcript, generating mutant proteins resulting in the appearance of pseudo-prototrophs in nondividing cells (4,22,37).…”
Section: Vol 192 2010 Stress-induced Mutagenesis In B Subtilis Celmentioning
confidence: 99%